Unreal Engine 4 Shaders and Effects Cookbook : Over 70 Recipes for Mastering Post-Processing Effects and Advanced Shading Techniques - Brenlla Ramos, Brais (Packt Publishing, Limited, 2019)
Unreal Shaders and Effects Cookbook is the first of its kind to bring you the secrets of creating Shaders for Unreal. This book guides you through the process of creating almost any conceivable material while understanding at the same time what happens under the hood - from the PBR workflow to using many of the very useful nodes Unreal includes.